HUBUNGAN KUALITAS TIDUR DENGAN KEJADIAN PENINGKATAN TEKANAN DARAH PASIEN PRE OPERASI - Riyadi, Raden Sugeng; Apriyani, Risma Dwi (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Purpose: This study aimed at determining the relationship between sleep quality and the occurrence of increased blood pressure in preoperative patients. Methods: The research method is the quantitative method with a correlational study approach. The sampling technique used was purposing sampling with a total of 68 respondents according to the inclusion and exclusion criteria. The data collection method was the observational analytic method and the data analysis used the Eta correlation test. Results: The results of the Eta correlation test to find out the relationship between sleep quality and increased blood pressure showed a p-value of 0.003<0.05 meaning that there was a significant relationship between sleep quality and increased blood pressure. The majority of the respondents had bad sleep quality as many as 36 respondents (52.9%) and most of them who had an increase in blood pressure of 20-50% were 36 respondents (52.9%). Conclusion: There is a significant relationship between sleep quality and increased blood pressure in preoperative patients. The results of the Eta test showed a p-value of 0.003 indicating a significant relationship between sleep quality and increased blood pressure.